PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, E-GOVERNMENT DAN ORGANISASI AGILITY TERHADAP MOTIVASI KERJA KARYAWAN DI LINGKUNGAN POLITEKNIK ILMU PEMASYARAKATAN DALAM MENGHADAPI ERA NEW NORMAL - Eka Fitri Setiawan (2022)
This study analyzes work motivation in the Penitentiary Polytechnic Environment. The purpose of this research is to prove and analyze the effect of transformational leadership, e-government and organizational agility on employee work motivation in the correctional science polytechnic environment in the face of the new normal era. This research is qualitative by distributing it to 50 employees in the Polytechnic of Correctional Sciences. This study uses the Partial Least Square (PLS) method with the Smart-PLS 3.0 program. The results of data analysis show that: (1) Transformational leadership has no significant effect on the work motivation of correctional science polytechnic employees in facing the new normal era (2) E-government has a significant effect on work motivation of correctional science polytechnic employees in facing the new normal era (3) Organization agility has no significant effect on work motivation of penitentiary polytechnic employees in facing the new normal era and (4) transformational leadership, e-government and organizational agility simultaneously significantly influence work motivation of correctional science polytechnic employees in facing the new normal era